Environment-friendly fully-synthetic magnesium alloy cutting fluid and preparation process thereof
By introducing perfluorohexanone and triphenyl phosphate into the magnesium alloy cutting fluid, the problems of high temperature flammability, short service life, oil-water separation and environmental pollution in magnesium alloy cutting fluid are solved, and the efficient performance of environmentally friendly fully synthesized cutting fluid is achieved.
Patent Information
- Application Number
- CN202510064554.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
Magnesium alloys produce high temperatures and flammable during cutting processing. The existing cutting fluid has a short service life, which can easily lead to oil-water separation, complex waste liquid treatment, and great environmental pollution.
The environmentally friendly fully synthetic magnesium alloy cutting fluid is used, including water-soluble extreme pressure antiwear agents, lubricants, anti-rust agents, corrosion inhibitors, anti-hard water agents, cationic surfactants, additives and microcapsules. The capsule core material of the microcapsule is a mixture of perfluorohexanone and triphenyl phosphate, and the capsule wall is modified chitosan. It is prepared by a spray device to ensure the uniform dispersion and stability of the microcapsule in the cutting fluid.
The cutting fluid has excellent comprehensive performance, which can effectively reduce the high temperature and combustion risks during cutting of magnesium alloys, extend the service life, reduce the difficulty of waste liquid treatment, reduce environmental pollution, and have good anti-rust, corrosion inhibition and flame retardant effects.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fully synthetic cutting fluids, and in particular to an environmentally friendly fully synthetic magnesium alloy cutting fluid and a preparation process thereof. Background Art
[0002] Magnesium alloy is an alloy composed of magnesium and other elements. Compared with carbon steel, copper and aluminum alloy, it has unique properties and has been widely used in the electronics industry, aerospace industry, automobile industry, machinery manufacturing industry, etc. in recent years. The processing scale of magnesium alloy parts has gradually expanded. During the cutting process of magnesium alloy parts, due to its relatively low ignition point, between 500℃ and 600℃, the heat generated between the milling cutter and the magnesium alloy can easily cause the magnesium alloy debris to burn or even explode. The burning of magnesium alloy debris is very easy to occur during the processing, so it is necessary to prevent and eliminate the occurrence of fire during the processing of magnesium alloy to ensure the safety of production.
[0003] Since magnesium alloys generate very high heat during cutting, high requirements are placed on the cooling and lubrication properties of cutting fluids. At the same time, magnesium is extremely chemically active, and yellow spots and white spots are prone to appear after cutting, affecting the appearance and even mechanical properties of the workpiece. In order to avoid corrosion of magnesium alloys during processing, cutting oil was mainly used for cutting of magnesium alloys in the early years. Cutting oil has very good lubricity and corrosion inhibition, but its service life is short and needs to be replaced frequently, resulting in more waste liquid discharge. There are many problems in environmental emissions and subsequent cleaning processes. In recent years, magnesium alloy cutting fluids are mainly emulsified oils and microemulsions. During use, magnesium is very active. Magnesium ions dissolved in water during the processing process will cause emulsifiers in the cutting fluid, such as sodium sulfonate, to become magnesium sulfonate. Magnesium sulfonate is not an emulsifier and cannot balance the emulsion system, resulting in emulsion and microemulsion demulsification and oil-water separation, which greatly reduces the service life of the cutting fluid. Moreover, emulsions and microemulsions have poor resistance to microorganisms, are prone to corruption and deterioration, and have a short fluid replacement cycle. At the same time, the treatment of waste liquids from emulsions and microemulsions is also very complicated, and waste liquid discharge has a great impact on environmental pollution.
[0004] Based on the above problems, the present invention provides an environmentally friendly fully synthetic magnesium alloy cutting fluid and its preparation process to overcome the problems of cutting oil, emulsion and microemulsion being flammable at high temperatures when cutting magnesium alloys, short service life of cutting oil, easy oil-water separation of emulsified cutting fluid during cutting, and serious environmental pollution caused by waste cutting fluid treatment. Summary of the invention
[0005] The purpose of the present invention is to provide an environmentally friendly fully synthetic magnesium alloy cutting fluid and a preparation process thereof. The environmentally friendly fully synthetic magnesium alloy cutting fluid has excellent comprehensive performance.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention provides an environmentally friendly fully synthetic magnesium alloy cutting fluid.
[0008] The invention comprises the following raw materials in proportion by mass fraction: 5-12% water-soluble extreme pressure anti-wear agent, 10-16% water-soluble lubricant, 4-10% water-soluble rust inhibitor, 0.5-1.5% magnesium alloy corrosion inhibitor, 2-4% anti-hard water agent, 1-3% cationic surfactant, 2-6% additive, 4-10% microcapsule, and the balance is deionized water;
[0009] The capsule core material of the microcapsule is a mixture of perfluorohexanone and triphenylphosphate, and the capsule wall of the microcapsule is modified chitosan;
[0010] The water-soluble rust preventive is triethanolamine citrate or di(triethanolamine)salt of sebacic acid, and the raw materials for preparing the water-soluble rust preventive are triethanolamine and citric acid or triethanolamine and sebacic acid.
[0011] Triphenyl phosphate is a multifunctional additive in cutting fluids. Its main functions in cutting fluids are as a rust inhibitor, corrosion inhibitor, flame retardant, lubricant and extreme pressure anti-wear agent. It also has the function of improving stability. However, since triphenyl phosphate is insoluble in water, it is subject to certain restrictions in fully synthetic cutting fluids. Perfluorohexanone is often used as the capsule core of microcapsules of fire extinguishing materials. When the target is on high temperature fire, it will break the capsule wall due to its low boiling point, and release it in a short time to reduce the temperature of the target position, thereby playing the role of extinguishing the fire and cooling down.
[0012] In the process of developing cutting fluid for magnesium alloy, the present invention creatively combines the characteristics of perfluorohexanone, and wraps perfluorohexanone and triphenyl phosphate in the capsule wall of the microcapsule. When the cutting fluid is not in use, the cutting fluid is stored at room temperature, and the perfluorohexanone will not overflow the microcapsule wall, so it is in a stable state. When in use, the microcapsule in contact with the cutting contact surface will vaporize and increase in volume due to the dual effects of high temperature and extrusion. After the capsule wall is broken, the perfluorohexanone is released to reduce the temperature of the cutting surface, greatly reducing the risk of high temperature and combustion and explosion. Along with the release of perfluorohexanone, triphenyl phosphate is also released, and it is accurately released on the cutting contact surface. On the one hand, it can increase the concentration of rust inhibitors, corrosion inhibitors, flame retardants, lubricants and extreme pressure anti-wear agents on the cutting contact surface, thereby reducing the rust on the cutting surface and further reducing the temperature of the cutting contact surface.
[0013] As a further preferred embodiment, in terms of weight ratio, the perfluorohexanone: the triphenylphosphate: the modified chitosan = 1: (1-5): (1-2).
[0014] As a further preferred embodiment, the water-soluble extreme pressure anti-wear agent is at least one of diethanolamine borate or triethanolamine borate.
[0015] As a further preferred embodiment, the water-soluble lubricant includes polyether ester and water-soluble trans-polyether.
[0016] As a further preferred embodiment, the magnesium alloy corrosion inhibitor includes alkyl phosphonate.
[0017] As a further preferred embodiment, the raw materials of the anti-hard water agent are tetrasodium ethylenediaminetetraacetate and alcohol ether carboxylic acid.
[0018] As a further preferred embodiment, the cationic surfactant includes one or more of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride and dodecyltrimethylammonium chloride.
[0019] As a further preferred embodiment, the auxiliary agent is isononanoic acid or octanoic acid.
[0020] As a further preferred embodiment, the modified chitosan is hydrophilic modified chitosan.
[0021] By using hydrophilic modified chitosan as the capsule wall of the microcapsule, on the one hand, the defect of triphenylphosphate being insoluble in water can be overcome, so that the microcapsules can be better and more evenly dispersed in the environmentally friendly fully synthetic magnesium alloy cutting fluid; on the other hand, since the hydrophilic modified chitosan has bactericidal, lubricating and wear-resistant properties, it can cooperate with the water-soluble extreme pressure anti-wear agent and water-soluble lubricant in the raw material to improve the overall performance of the cutting fluid.
[0022] The second aspect of the present invention provides a process for preparing an environmentally friendly fully synthetic magnesium alloy cutting fluid, comprising the following steps:
[0023] S1: Add triethanolamine to the reaction kettle, raise the temperature to 80°C, stop heating, add alcohol ether carboxylic acid under stirring, then add sebacic acid or citric acid, and stir for about 30 minutes until transparent;
[0024] S2: Add deionized water to the reaction kettle, add tetrasodium ethylenediaminetetraacetate and alcohol ether carboxylic acid under stirring, and stir for 10 minutes until they are completely dissolved;
[0025] S3: Add water-soluble lubricant, cationic polymer and additive into the reaction kettle, stir until transparent, and cool to room temperature to obtain a solution;
[0026] S4: preparing microcapsules, adding the microcapsules into the solution obtained in S3, and stirring evenly to obtain the environmentally friendly fully synthetic magnesium alloy cutting fluid.
[0027] As a further preferred embodiment, the microcapsule is prepared by the following steps:
[0028] S41, preparation of modified chitosan solution: slowly adding 4% by mass polyethylene glycol 6000 solution to 2% by mass chitosan solution of the same volume at room temperature, stirring evenly while adding; then continue stirring for 24 hours to allow polyethylene glycol 6000 to fully react with chitosan to form a modified chitosan solution;
[0029] S42, preparation of a core mixed solution: respectively prepare a gelatin GE solution with a mass fraction of 12-21% and a gum arabic GA solution with a mass fraction of 15-26%; stir and mix the perfluorohexanone and the 3 to obtain a mixture; mix the aforementioned gelatin GE solution, modified gum arabic GA solution and the mixture in a volume ratio of (7-9): (10-16): (8-10) to obtain the core mixed solution; wherein the gelatin GE solution and the gum arabic GA solution act together as emulsifiers to achieve an emulsification effect;
[0030] S43, spraying the core mixed solution obtained in S42 into the modified chitosan solution prepared in step S41 through a spray device with a spray port of 5-9 mm and a spray speed of 0.3-0.6 L / h, and emulsifying at room temperature for 10-25 min to form a stable emulsion;
[0031] S44, adding an acid-base regulator to the emulsion prepared in step S43 to adjust the pH value of the system to 6-8, adding a curing agent with a concentration of 5% after the pH value stabilizes, and performing a curing reaction at room temperature for 24 hours to obtain a microcapsule suspension;
[0032] S45, centrifuging, washing and drying the microcapsule suspension to obtain microcapsules with a particle size of 1-10 μm.
[0033] As a further preferred embodiment, the chitosan has an average molecular weight of 50-90 kDa and a deacetylation degree of ≥90% based on mass fraction.
[0034] As a further preferred embodiment, the chitosan solution is obtained by the following method: adding chitosan powder to a 1% acetic acid aqueous solution, stirring for 24 hours, and adjusting the pH value of the chitosan solution to 5.5 using a 1M NaOH solution to obtain a 2% chitosan solution.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1) The cutting fluid of the present invention is a fully synthetic cutting fluid, which is less difficult to handle than the microemulsion cutting fluid and has less impact on the environment than the microemulsion cutting fluid. It is a relatively environmentally friendly cutting fluid.
[0037] 2) The capsule wall of the microcapsule in the raw material of the environmentally friendly fully synthetic magnesium alloy cutting fluid of the present invention is hydrophilically modified chitosan, so that the microcapsule structure as a whole can be well dispersed in water, and after the triphenyl phosphate is wrapped, the problem that the triphenyl phosphate is insoluble in water and difficult to be evenly dispersed in the fully synthetic cutting fluid is overcome. At the same time, the hydrophilically modified chitosan has the properties of sterilization, lubrication and wear resistance, and can cooperate with the water-soluble extreme pressure anti-wear agent and water-soluble lubricant in the raw material to improve the overall performance of the cutting fluid.
[0038] 3) Perfluorohexanone has a low vaporization temperature. The present invention creatively applies this property of perfluorohexanone. When the cutting fluid is not used and stored at room temperature, the perfluorohexanone will not overflow in the capsule wall and will be in a relatively stable state as a whole. When the cutting fluid is used for cutting of magnesium alloys, the microcapsule structure of the processing contact surface is affected by the high temperature caused by extrusion and cutting. At least part of the perfluorohexanone will vaporize and burst the capsule wall. After the perfluorohexanone overflows, the liquid perfluorohexanone that has not yet vaporized can quickly absorb heat and reduce the temperature of the cutting contact surface, achieving a good cooling effect. In addition, along with the overflow of perfluorohexanone, triphenylphosphate also overflows to the cutting contact surface, and it is accurately released on the cutting contact surface. On the one hand, it can increase the concentration of rust inhibitors, corrosion inhibitors, lubricants and extreme pressure anti-wear agents on the cutting contact surface. , thereby reducing the rust on the cutting surface, that is to say, to a certain extent, the problems of corrosion and rust on the freshly cut surface of the magnesium alloy are solved. On the other hand, triphenyl phosphate, as an excellent phosphorus-based flame retardant, can form a protective film on the cutting contact surface when it is precisely released on the cutting surface due to the effect of perfluorohexanone, thereby preventing the cutting contact surface from contacting with oxygen. Since the combustion temperature is lowered by perfluorohexanone, and the oxygen necessary for combustion is at least partially isolated by triphenyl phosphate, the two core materials of the microcapsule work together to achieve a better flame retardant effect.
[0039] 4) The microcapsule preparation process of the invention can control the size of the microcapsule. In order to obtain microcapsules with a particle size suitable for cutting fluid, the emulsifier and the capsule core material are first mixed, and then sprayed into a hydrophilic modified chitosan solution for emulsification. The size of the microcapsule is controlled by adjusting the size of the nozzle and the spraying rate. DETAILED DESCRIPTION
[0040] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0041] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0042] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Example 1
[0044] The raw materials of the environmentally friendly fully synthetic magnesium alloy cutting fluid of Example 1 are as follows:
[0045] 8g triethanolamine borate, 6g polyether ester, 7g water-soluble trans-polyether, 8g triethanolamine, 3g citric acid, 2g tetrasodium ethylenediaminetetraacetic acid, 2g alcohol ether carboxylic acid, 1g alkyl phosphonate, 2g hexadecyltrimethylammonium bromide, 4g octanoic acid, 7g microcapsule, 50g deionized water;
[0046] The capsule core material of the microcapsule is a mixture of perfluorohexanone and triphenylphosphate, and the capsule wall of the microcapsule is modified chitosan;
[0047] The preparation process of the environmentally friendly fully synthetic magnesium alloy cutting fluid of Example 1 is as follows:
[0048] S1: Add triethanolamine to the reaction kettle according to the mass ratio of the raw materials, raise the temperature to 80°C, stop heating, add ether carboxylic acid ammonium salt and citric acid under stirring, and stir for about 30 minutes until transparent;
[0049] S2: adding deionized water to the reaction kettle, adding tetrasodium ethylenediaminetetraacetate under stirring, and stirring for 10 minutes until it is completely dissolved to obtain a mixture of ether carboxylic acid ammonium salt and triethanolamine citrate;
[0050] S3: Add polyether ester and water-soluble trans-polyether, hexadecyltrimethylammonium bromide and octanoic acid into the reaction kettle, stir until transparent, and cool to room temperature to obtain a solution;
[0051] S4: Preparation of microcapsules:
[0052] S41, preparation of modified chitosan solution: select chitosan with an average molecular weight of 50-90kDa and a deacetylation degree of ≥90% as a raw material, add chitosan powder to a 1% acetic acid aqueous solution, stir for 24 hours, adjust the pH value of the chitosan solution to 5.5 with a 1MNaOH solution, and obtain a 2% chitosan solution; slowly add a 4% polyethylene glycol 6000 solution to the same volume of a 2% chitosan solution at room temperature, stirring evenly while adding; then continue stirring for 24 hours to allow the polyethylene glycol 6000 to fully react with the chitosan to form a modified chitosan solution;
[0053] S42, preparation of a core mixed solution: prepare a gelatin GE solution with a mass fraction of 17% and a gum arabic GA solution with a mass fraction of 20% respectively; stir and mix the perfluorohexanone and the triphenylphosphate in a mass ratio of 1:2.5 to obtain a mixture; mix the prepared gelatin GE solution, the modified gum arabic GA solution and the mixture in a volume ratio of 8:13:9 to obtain the core mixed solution; wherein the gelatin GE solution and the gum arabic GA solution together act as a second emulsifier to play an emulsifying role;
[0054] S43, under the condition that the mass ratio of the raw material of the core to the raw material of the shell is 11:6, the core mixed solution prepared in S42 is sprayed into the modified chitosan solution prepared in step S41 through a spray device with a spray port of 7 mm and a spray speed of 0.4 L / h, and emulsified at room temperature for 10-25 min to form a stable emulsion;
[0055] S44, adding an acid-base regulator to the emulsion prepared in step S43 to adjust the pH value of the system to 6-8, adding 5% glutaraldehyde as a curing agent after the pH value stabilizes, and performing a curing reaction at room temperature for 24 hours to obtain a microcapsule suspension;
[0056] S45, centrifuging, washing, and drying the microcapsule suspension to obtain microcapsules with a particle size of 1-10 μm;
[0057] The microcapsules are added into the solution obtained in S3, and stirred evenly to obtain the environmentally friendly fully synthetic magnesium alloy cutting fluid.
[0058] Example 2
[0059] The raw materials of the environmentally friendly fully synthetic magnesium alloy cutting fluid of Example 2 are as follows:
[0060] 8g triethanolamine borate, 6g polyether ester, 7g water-soluble trans-polyether, 8g triethanolamine, 3g citric acid, 2g tetrasodium ethylenediaminetetraacetic acid, 2g alcohol ether carboxylic acid, 1g alkyl phosphonate, 2g hexadecyltrimethylammonium bromide, 4g octanoic acid, 7g microcapsule, 50g deionized water;
[0061] The capsule core material of the microcapsule is a mixture of perfluorohexanone and triphenylphosphate, and the capsule wall of the microcapsule is modified chitosan;
[0062] The preparation process of the environmentally friendly fully synthetic magnesium alloy cutting fluid of Example 2 is as follows:
[0063] S1: Add triethanolamine to the reaction kettle according to the mass ratio of the raw materials, raise the temperature to 80°C, stop heating, add ether carboxylic acid ammonium salt and citric acid under stirring, and stir for about 30 minutes until transparent;
[0064] S2: adding deionized water to the reaction kettle, adding tetrasodium ethylenediaminetetraacetate under stirring, and stirring for 10 minutes until it is completely dissolved to obtain a mixture of ether carboxylic acid ammonium salt and triethanolamine citrate;
[0065] S3: Add polyether ester and water-soluble trans-polyether, hexadecyltrimethylammonium bromide and octanoic acid into the reaction kettle, stir until transparent, and cool to room temperature to obtain a solution;
[0066] S4: Preparation of microcapsules:
[0067] S41, preparation of modified chitosan solution: select chitosan with an average molecular weight of 50-90kDa and a deacetylation degree of ≥90% as a raw material, add chitosan powder to a 1% acetic acid aqueous solution, stir for 24 hours, adjust the pH value of the chitosan solution to 5.5 with a 1MNaOH solution, and obtain a 2% chitosan solution; slowly add a 4% polyethylene glycol 6000 solution to the same volume of a 2% chitosan solution at room temperature, stirring evenly while adding; then continue stirring for 24 hours to allow the polyethylene glycol 6000 to fully react with the chitosan to form a modified chitosan solution;
[0068] S42, preparation of a core mixed solution: prepare a gelatin GE solution with a mass fraction of 17% and a gum arabic GA solution with a mass fraction of 20% respectively; stir and mix the perfluorohexanone and the triphenylphosphate in a mass ratio of 1:1 to obtain a mixture; mix the prepared gelatin GE solution, the modified gum arabic GA solution and the mixture in a volume ratio of 7:8:10 to obtain the core mixed solution; wherein the gelatin GE solution and the gum arabic GA solution together act as a second emulsifier to play an emulsifying role;
[0069] S43, under the condition that the mass ratio of the raw material of the core to the raw material of the shell is 8:5, the core mixed solution prepared in S42 is sprayed into the modified chitosan solution prepared in step S41 through a spray device with a spray port of 5 mm and a spray speed of 0.4 L / h, and emulsified at room temperature for 10-25 min to form a stable emulsion;
[0070] S44, adding an acid-base regulator to the emulsion prepared in step S43 to adjust the pH value of the system to 6-8, adding 5% glutaraldehyde as a curing agent after the pH value stabilizes, and performing a curing reaction at room temperature for 24 hours to obtain a microcapsule suspension;
[0071] S45, centrifuging, washing, and drying the microcapsule suspension to obtain microcapsules with a particle size of 1-10 μm;
[0072] The microcapsules are added into the solution obtained in S3, and stirred evenly to obtain the environmentally friendly fully synthetic magnesium alloy cutting fluid.
[0073] Example 3
[0074] The raw materials of the environmentally friendly fully synthetic magnesium alloy cutting fluid of Example 3 are as follows:
[0075] 8g triethanolamine borate, 6g polyether ester, 7g water-soluble trans-polyether, 8g triethanolamine, 3g citric acid, 2g tetrasodium ethylenediaminetetraacetic acid, 2g alcohol ether carboxylic acid, 1g alkyl phosphonate, 2g hexadecyltrimethylammonium bromide, 4g octanoic acid, 7g microcapsule, 50g deionized water;
[0076] The capsule core material of the microcapsule is a mixture of perfluorohexanone and triphenylphosphate, and the capsule wall of the microcapsule is modified chitosan;
[0077] The preparation process of the environmentally friendly fully synthetic magnesium alloy cutting fluid of Example 2 is as follows:
[0078] S1: Add triethanolamine to the reaction kettle according to the mass ratio of the raw materials, raise the temperature to 80°C, stop heating, add ether carboxylic acid ammonium salt and citric acid under stirring, and stir for about 30 minutes until transparent;
[0079] S2: adding deionized water to the reaction kettle, adding tetrasodium ethylenediaminetetraacetate under stirring, and stirring for 10 minutes until it is completely dissolved to obtain a mixture of ether carboxylic acid ammonium salt and triethanolamine citrate;
[0080] S3: Add polyether ester and water-soluble trans-polyether, hexadecyltrimethylammonium bromide and octanoic acid into the reaction kettle, stir until transparent, and cool to room temperature to obtain a solution;
[0081] S4: Preparation of microcapsules:
[0082] S41, preparation of modified chitosan solution: select chitosan with an average molecular weight of 50-90kDa and a deacetylation degree of ≥90% as a raw material, add chitosan powder to a 1% acetic acid aqueous solution, stir for 24 hours, adjust the pH value of the chitosan solution to 5.5 with a 1MNaOH solution, and obtain a 2% chitosan solution; slowly add a 4% polyethylene glycol 6000 solution to the same volume of a 2% chitosan solution at room temperature, stirring evenly while adding; then continue stirring for 24 hours to allow the polyethylene glycol 6000 to fully react with the chitosan to form a modified chitosan solution;
[0083] S42, preparation of a core mixed solution: prepare a gelatin GE solution with a mass fraction of 17% and a gum arabic GA solution with a mass fraction of 20% respectively; stir and mix the perfluorohexanone and the triphenylphosphate in a mass ratio of 1:5 to obtain a mixture; mix the prepared gelatin GE solution, the modified gum arabic GA solution and the mixture in a volume ratio of 9:16:10 to obtain the core mixed solution; wherein the gelatin GE solution and the gum arabic GA solution together act as a second emulsifier to play an emulsifying role;
[0084] S43, under the condition that the mass ratio of the raw material of the core to the raw material of the shell is 13:7, the core mixed solution prepared in S42 is sprayed into the modified chitosan solution prepared in step S41 through a spray device with a spray port of 9 mm and a spray speed of 0.4 L / h, and emulsified at room temperature for 10-25 min to form a stable emulsion;
[0085] S44, adding an acid-base regulator to the emulsion prepared in step S43 to adjust the pH value of the system to 6-8, adding 5% glutaraldehyde as a curing agent after the pH value stabilizes, and performing a curing reaction at room temperature for 24 hours to obtain a microcapsule suspension;
[0086] S45, centrifuging, washing, and drying the microcapsule suspension to obtain microcapsules with a particle size of 1-10 μm;
[0087] The microcapsules are added into the solution obtained in S3, and stirred evenly to obtain the environmentally friendly fully synthetic magnesium alloy cutting fluid.
[0088] Example 4
[0089] The raw materials of the environmentally friendly fully synthetic magnesium alloy cutting fluid of Example 4 are as follows:
[0090] 7g triethanolamine borate, 7g polyether ester, 4g water-soluble trans-polyether, 8g triethanolamine, 3g citric acid, 2g tetrasodium ethylenediaminetetraacetic acid, 2g alcohol ether carboxylic acid, 1g alkyl phosphonate, 2g hexadecyltrimethylammonium bromide, 4g octanoic acid, 10g microcapsule, 50g deionized water;
[0091] The capsule core material of the microcapsule is a mixture of perfluorohexanone and triphenylphosphate, and the capsule wall of the microcapsule is modified chitosan;
[0092] The preparation process of the environmentally friendly fully synthetic magnesium alloy cutting fluid of Example 4 is as follows:
[0093] S1: Add triethanolamine to the reaction kettle according to the mass ratio of the raw materials, raise the temperature to 80°C, stop heating, add ether carboxylic acid ammonium salt and citric acid under stirring, and stir for about 30 minutes until transparent;
[0094] S2: adding deionized water to the reaction kettle, adding tetrasodium ethylenediaminetetraacetate under stirring, and stirring for 10 minutes until it is completely dissolved to obtain a mixture of ether carboxylic acid ammonium salt and triethanolamine citrate;
[0095] S3: Add polyether ester and water-soluble trans-polyether, hexadecyltrimethylammonium bromide and octanoic acid into the reaction kettle, stir until transparent, and cool to room temperature to obtain a solution;
[0096] S4: Preparation of microcapsules:
[0097] S41, preparation of modified chitosan solution: select chitosan with an average molecular weight of 50-90kDa and a deacetylation degree of ≥90% as a raw material, add chitosan powder to a 1% acetic acid aqueous solution, stir for 24 hours, adjust the pH value of the chitosan solution to 5.5 with a 1MNaOH solution, and obtain a 2% chitosan solution; slowly add a 4% polyethylene glycol 6000 solution to the same volume of a 2% chitosan solution at room temperature, stirring evenly while adding; then continue stirring for 24 hours to allow the polyethylene glycol 6000 to fully react with the chitosan to form a modified chitosan solution;
[0098] S42, preparation of a core mixed solution: prepare a gelatin GE solution with a mass fraction of 17% and a gum arabic GA solution with a mass fraction of 20% respectively; stir and mix the perfluorohexanone and the triphenylphosphate in a mass ratio of 1:2.5 to obtain a mixture; mix the prepared gelatin GE solution, the modified gum arabic GA solution and the mixture in a volume ratio of 8:13:9 to obtain the core mixed solution; wherein the gelatin GE solution and the gum arabic GA solution together act as a second emulsifier to play an emulsifying role;
[0099] S43, under the condition that the mass ratio of the raw material of the core to the raw material of the shell is 11:6, the core mixed solution prepared in S42 is sprayed into the modified chitosan solution prepared in step S41 through a spray device with a spray port of 5 mm and a spray speed of 0.4 L / h, and emulsified at room temperature for 10-25 min to form a stable emulsion;
[0100] S44, adding an acid-base regulator to the emulsion prepared in step S43 to adjust the pH value of the system to 6-8, adding 5% glutaraldehyde as a curing agent after the pH value stabilizes, and performing a curing reaction at room temperature for 24 hours to obtain a microcapsule suspension;
[0101] S45, centrifuging, washing, and drying the microcapsule suspension to obtain microcapsules with a particle size of 1-10 μm;
[0102] The microcapsules are added into the solution obtained in S3, and stirred evenly to obtain the environmentally friendly fully synthetic magnesium alloy cutting fluid.
[0103] Example 5
[0104] The raw materials of the environmentally friendly fully synthetic magnesium alloy cutting fluid of Example 5 are as follows:
[0105] 8g triethanolamine borate, 7g polyether ester, 7g water-soluble trans-polyether, 8g triethanolamine, 3g citric acid, 2g tetrasodium ethylenediaminetetraacetic acid, 2g alcohol ether carboxylic acid, 1g alkyl phosphonate, 2g hexadecyltrimethylammonium bromide, 4g octanoic acid, 4g microcapsule, 52g deionized water;
[0106] The capsule core material of the microcapsule is a mixture of perfluorohexanone and triphenylphosphate, and the capsule wall of the microcapsule is modified chitosan;
[0107] The preparation process of the environmentally friendly fully synthetic magnesium alloy cutting fluid of Example 5 is as follows:
[0108] S1: Add triethanolamine to the reaction kettle according to the mass ratio of the raw materials, raise the temperature to 80°C, stop heating, add ether carboxylic acid ammonium salt and citric acid under stirring, and stir for about 30 minutes until transparent;
[0109] S2: adding deionized water to the reaction kettle, adding tetrasodium ethylenediaminetetraacetate under stirring, and stirring for 10 minutes until it is completely dissolved to obtain a mixture of ether carboxylic acid ammonium salt and triethanolamine citrate;
[0110] S3: Add polyether ester and water-soluble trans-polyether, hexadecyltrimethylammonium bromide and octanoic acid into the reaction kettle, stir until transparent, and cool to room temperature to obtain a solution;
[0111] S4: Preparation of microcapsules:
[0112] S41, preparation of modified chitosan solution: select chitosan with an average molecular weight of 50-90kDa and a deacetylation degree of ≥90% as a raw material, add chitosan powder to a 1% acetic acid aqueous solution, stir for 24 hours, adjust the pH value of the chitosan solution to 5.5 with a 1MNaOH solution, and obtain a 2% chitosan solution; slowly add a 4% polyethylene glycol 6000 solution to the same volume of a 2% chitosan solution at room temperature, stirring evenly while adding; then continue stirring for 24 hours to allow the polyethylene glycol 6000 to fully react with the chitosan to form a modified chitosan solution;
[0113] S42, preparation of a core mixed solution: prepare a gelatin GE solution with a mass fraction of 17% and a gum arabic GA solution with a mass fraction of 20% respectively; stir and mix the perfluorohexanone and the triphenylphosphate in a mass ratio of 1:2.5 to obtain a mixture; mix the prepared gelatin GE solution, the modified gum arabic GA solution and the mixture in a volume ratio of 8:13:9 to obtain the core mixed solution; wherein the gelatin GE solution and the gum arabic GA solution together act as a second emulsifier to play an emulsifying role;
[0114] S43, under the condition that the mass ratio of the raw material of the core to the raw material of the shell is 11:6, the core mixed solution prepared in S42 is sprayed into the modified chitosan solution prepared in step S41 through a spray device with a spray port of 5 mm and a spray speed of 0.4 L / h, and emulsified at room temperature for 10-25 min to form a stable emulsion;
[0115] S44, adding an acid-base regulator to the emulsion prepared in step S43 to adjust the pH value of the system to 6-8, adding 5% glutaraldehyde as a curing agent after the pH value stabilizes, and performing a curing reaction at room temperature for 24 hours to obtain a microcapsule suspension;
[0116] S45, centrifuging, washing, and drying the microcapsule suspension to obtain microcapsules with a particle size of 1-10 μm;
[0117] The microcapsules are added into the solution obtained in S3, and stirred evenly to obtain the environmentally friendly fully synthetic magnesium alloy cutting fluid.
[0118] Comparative Example 1
[0119] The difference between the comparative example and Example 1 is that the weight of the microcapsule is 2 g, and the rest is the same as Example 1.
[0120] Comparative Example 2
[0121] The difference between the comparative example and Example 1 is that the microcapsules only use an equal amount of modified chitosan, and the rest are the same as Example 1.
[0122] Comparative Example 3
[0123] The difference between the comparative example and Example 1 is that the microcapsules only use an equal amount of deionized water, and the rest is the same as Example 1.
[0124] Microcapsule particle size test and cutting fluid appearance inspection:
[0125] The average particle size of the microcapsules of Examples 1, 4-5 is 5 μm, the average particle size of the microcapsules of Example 2 is 1 μm, and the average particle size of the microcapsules of Example 3 is 8 μm; in appearance, both Examples 1-5 and Comparative Examples 1-3 are solutions without precipitation.
[0126] Cooling performance test:
[0127] The concentration of each sample in the test was 6%, and the initial pH was 9.5. The cutting fluid was used to process the specimens. The samples were used to continuously cut 3 specimens at the same time point every 2 days, which was recorded as 1 time. This was repeated 20 times, i.e., the experimental period was 60 days. The same specimen material was used for each cutting, which was magnesium alloy AZ91D bar stock. The processing was to extrude internal threads on the bar stock. The holes were drilled with a drill bit, and the spindle speed was 100r / min. After drilling, the extrusion tap was used for extrusion processing. When extruding the threads, the spindle rotation speed was controlled at 30-80r / min to obtain the magnesium alloy AZ91D internal threads. The highest temperature during the 1st, 5th, 10th, 15th and 20th cutting processes was recorded by thermocouples.
[0128] Table 1 Antibacterial performance test results
[0129] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 The first maximum temperature 44℃ 43.8℃ 44.5℃ 42.3℃ 45.1℃ 65.4℃ 68.2℃ 68.3℃ The 5th highest temperature 46.9℃ 47℃ 47.2℃ 44.8℃ 47.7℃ 69.8℃ 76.5℃ 77.1℃ 10th highest temperature 49.7℃ 49.5℃ 50.1℃ 48.6℃ 51.4℃ 75.5℃ 85.1℃ 84.8℃ 15th highest temperature 52.8℃ 52.7℃ 53.6℃ 51.1℃ 54.5℃ 81.6℃ 91.4℃ 90.5℃ 20th highest temperature 54.5℃ 54.4℃ 55℃ 53.2℃ 55.9℃ 85.9℃ 105℃ 104.8℃
[0130] Comparative Examples 1-5 show that the particle size of the core-shell particles can be increased by increasing the size of the nozzle, thereby obtaining a particle size suitable for microemulsion cutting fluid.
[0131] According to the test results, the microcapsule addition amount of 4-10% can be well dissolved in the environmentally friendly fully synthetic magnesium alloy cutting fluid; when the content is lower than this content, referring to Comparative Example 1, due to the low content of microcapsules, the microcapsules in contact with the cutting surface are less, and the content of perfluorohexanone and triphenylphosphate that are squeezed and released is less. Although there is a weak cooling effect, the maximum cutting temperature is still greatly increased after multiple uses. The maximum temperature exceeds 80°C during the 20th processing, which affects the processing of magnesium alloy. Examples 1-5 all obtain environmentally friendly fully synthetic magnesium alloy cutting fluids. Compared with Comparative Examples 2 and 3, although Comparative Example 2 uses modified chitosan and Comparative Example 3 replaces microcapsules with deionized water, with the increase of the number of cutting times, the effect of chitosan or deionized water on reducing the maximum cutting temperature is not obvious. The maximum temperature exceeds 100°C during the 20th processing. If it is processed multiple times and applied in more complex processing conditions, the temperature will increase more, which seriously reduces the processing safety of magnesium alloy.
[0132] The above is a detailed introduction to an environmentally friendly fully synthetic magnesium alloy cutting fluid and its preparation process disclosed in the embodiment of the present application. The above content is a further detailed description of the present invention in combination with a specific preferred embodiment, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, its architecture can be flexible and can derive a series of products. Just making a few simple deductions or substitutions should be regarded as belonging to the scope of patent protection of the present invention determined by the submitted claims.
Claims
1. An environmentally friendly fully synthetic magnesium alloy cutting fluid, characterized in that: The invention comprises the following raw materials in proportion by mass fraction: 5-12% water-soluble extreme pressure anti-wear agent, 10-16% water-soluble lubricant, 4-10% water-soluble rust inhibitor, 0.5-1.5% magnesium alloy corrosion inhibitor, 2-4% anti-hard water agent, 1-3% cationic surfactant, 2-6% additive, 4-10% microcapsule, and the balance is deionized water; The capsule core material of the microcapsule is a mixture of perfluorohexanone and triphenylphosphate, and the capsule wall of the microcapsule is modified chitosan; The water-soluble rust preventive is triethanolamine citrate or di(triethanolamine)salt of sebacic acid, and the raw materials for preparing the water-soluble rust preventive are triethanolamine and citric acid or triethanolamine and sebacic acid.
2. The environmentally friendly fully synthetic magnesium alloy cutting fluid according to claim 1, characterized in that: According to the weight ratio, the perfluorohexanone: the triphenyl phosphate: the modified chitosan = 1: (1-5):(1-2)。 3. The environmentally friendly fully synthetic magnesium alloy cutting fluid according to claim 2, characterized in that: The water-soluble extreme pressure anti-wear agent is at least one of diethanolamine borate or triethanolamine borate; The water-soluble lubricant includes polyether ester and water-soluble trans-polyether.
4. The environmentally friendly fully synthetic magnesium alloy cutting fluid according to claim 3, characterized in that: The magnesium alloy corrosion inhibitor includes an alkyl phosphonate; The raw materials of the anti-hard water agent are tetrasodium ethylenediaminetetraacetate and alcohol ether carboxylic acid.
5. The environmentally friendly fully synthetic magnesium alloy cutting fluid according to claim 4, characterized in that: The cationic surfactant includes one or more of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride and dodecyltrimethylammonium chloride; The auxiliary agents are isononanoic acid and octanoic acid.
6. The environmentally friendly fully synthetic magnesium alloy cutting fluid according to any one of claims 1 to 5, characterized in that: The modified chitosan is hydrophilic modified chitosan.
7. A process for preparing the environmentally friendly fully synthetic magnesium alloy cutting fluid according to claim 6, characterized in that: The steps include: S1: Add triethanolamine to the reaction kettle, raise the temperature to 80°C, stop heating, add alcohol ether carboxylic acid under stirring, then add sebacic acid or citric acid, and stir for about 30 minutes until transparent; S2: Add deionized water to the reaction kettle, add tetrasodium ethylenediaminetetraacetate and alcohol ether carboxylic acid under stirring, and stir for 10 minutes until they are completely dissolved; S3: Add water-soluble lubricant, cationic polymer and additive into the reaction kettle, stir until transparent, and cool to room temperature to obtain a solution; S4: preparing microcapsules, adding the microcapsules into the solution obtained in S3, and stirring evenly to obtain the environmentally friendly fully synthetic magnesium alloy cutting fluid.
8. The process for preparing the environmentally friendly fully synthetic magnesium alloy cutting fluid according to claim 7, characterized in that: The microcapsules are prepared by the following steps: S41, preparation of modified chitosan solution: slowly adding 4% by mass polyethylene glycol 6000 solution to 2% by mass chitosan solution of the same volume at room temperature, stirring evenly while adding; then continue stirring for 24 hours to allow polyethylene glycol 6000 to fully react with chitosan to form a modified chitosan solution; S42, preparation of a core mixed solution: prepare gelatin GE solution and gum arabic GA solution with a mass fraction of 12-21% and 15-26% respectively; stir and mix the perfluorohexanone and the triphenylphosphate to obtain a mixture; mix the gelatin GE solution, the modified gum arabic GA solution and the mixture in a volume ratio of (7-9): (10-16): (8-10) to obtain the core mixed solution; wherein the gelatin GE solution and the gum arabic GA solution act together as emulsifiers to achieve an emulsification effect; S43, spraying the core mixed solution obtained in S42 into the modified chitosan solution prepared in step S41 through a spray device with a spray port of 5-9 mm and a spray speed of 0.3-0.6 L / h, and emulsifying at room temperature for 10-25 min to form a stable emulsion; S44, adding an acid-base regulator to the emulsion prepared in step S43 to adjust the pH value of the system to 6-8, adding a curing agent with a concentration of 5% after the pH value stabilizes, and performing a curing reaction at room temperature for 24 hours to obtain a microcapsule suspension; S45, centrifuging, washing and drying the microcapsule suspension to obtain microcapsules with a particle size of 1-10 μm.
9. The process for preparing the environmentally friendly fully synthetic magnesium alloy cutting fluid according to claim 8, characterized in that: According to mass fraction, the average molecular weight of the chitosan is 50-90 kDa, and the degree of deacetylation is ≥90%.
10. The process for preparing the environmentally friendly fully synthetic magnesium alloy cutting fluid according to claim 8, characterized in that: The chitosan solution is obtained by the following method: adding chitosan powder to 1% acetic acid aqueous solution, stirring for 24 hours, and adjusting the pH value of the chitosan solution to 5.5 using 1M NaOH solution to obtain a 2% chitosan solution.